Spatio-Temporal Variations of Surface Melt Over Antarctic Ice Shelves using SCATSAT-1 Data - Pooja Mishra; Naveen Tripathi; S. R. Oza; P. M. Solanki; N. Y. Bhatt (International Journal of Scientific Research in Science and Technology, 2024)
Surface melting is a significant issue in Antarctica, affecting glacier movements and climate change. During summer, surface meltwaters from ponds circulate over ice shelves, causing mass loss. These melt water percolates down to shelf through crevasses and affects the iceshelf instability or break the ice shelf. Antarctica experiences a surface melting increase of around 3.5 million square kilometres for every one-degree rise in summer temperature. In this study we use remote-sensing data sets to assess the spatial and temporal distribution of surface melt over Antarctic ice shelves. We use microwave brightness temperature (Tb) to evaluate surface melting on ice shelves. Total four ice shelves from East and West Antarctica were selected for research due to their significant surface melting issues. The study estimated cumulative melt days over these ice shelves for year 2017 and 2018, and investigated melt variations over transect profiles. It was found that year 2018 showed increased amount in melt days in some regions of selected ice shelves.
Keywords: Antarctica, Ice Shelf; Remote Sensing; Surface Melt; SCATSAT-1